Prevalence of Listeria species in camel sausages from retail markets in Aydin province in Turkey and RAPD analysis of Listeria monocytogenes isolates - Ozbey, Gokben; Ertas, Hasan Basri; Kok, Filiz (Bmc, 2006)
Samples were taken from 100 camel sausages from the different retail markets in Aydin province in the south-west of Turkey and they were tested for the presence of Listeria spp by biochemical methods. Samples were enriched using Listeria Enrichment Broth and they were inoculated onto Listeria Selective Agar Listeria monocytogenes was isolated from nine samples (9%), Listeria innocua from 14 samples (14%) and Listeria welshimeri from two samples(2%). A 701 bp fragment of listeriolysin 0 sequence for L. monocytogenes was amplified using specific primers by polymerase chain reaction (PCR) for confirmation of the identification. A random primer (OPA-11) was used in a random amplified polymorphic DNA (RAPD) assay This detected five different band profiles amongst the L. monocytogenes isolates, indicating a relatively large amount of genetic heterogeneity amongst the nine isolates. The study has highlighted the need for improved strategies for food safety, in particular appropriate hygienic precautions to avoid contamination of sausage during the manufacturing process and appropriate preservation techniques during storage and transport, to prevent transmission of Listeria spp to consumers at home and abroad.
Keywords: ccamel sausage; Listeria monocytogenes; PCR; RAPD